Transcriptional deregulation of stress-growth balance in Nicotiana benthamiana biofactories producing insect sex pheromones - Juteršek, Mojca; Petek, Marko; Ramšak, Živa; Moreno-Giménez, Elena; Gianoglio, Silvia; Mateos-Fernández, Rubén; Orzáez, Diego; Gruden, Kristina; Baebler, Špela (Frontiers in Plant Science, 2022)
Plant biofactories are a promising platform for sustainable production of high value compounds, among which are insect sex pheromones, a green alternative to conventional insecticides in agriculture. Recently, we have constructed transgenic Nicotiana benthamiana plants (“Sexy Plants”, SxP) that successfully produce a blend of moth (Lepidoptera) sex pheromone compounds (Z)-11-hexadecen-1-ol and (Z)-11-hexadecenyl acetate. However, efficient biosynthesis of sex pheromones resulted in growth and developmental penalty, diminishing the potential for commercial use of SxP in biomanufacturing. To gain insight into the underlying molecular responses, we analysed the whole-genome transcriptome and evaluated it in relation to growth and pheromone production in low and high producing transgenic plants of v1.0 and v1.2 SxP lines. In our study, high producing SxPv1.2 plants accumulated the highest amounts of pheromones but still maintained better growth compared to v1.0 high producers. For an in-depth biological interpretation of the transcriptomic data, we have prepared a comprehensive functional N. benthamiana genome annotation as well as gene translations to Arabidopsis thaliana, enabling functional information transfer by using Arabidopsis knowledge networks. Differential gene expression analysis, contrasting pheromone producers to wild type plants, revealed that while only a few genes were differentially regulated in low producing plants, high producing plants exhibited vast transcriptional reprogramming. They showed signs of stress-like response, manifested as downregulation of photosynthesis-related genes and significant differences in expression of hormonal signalling and secondary metabolism-related genes, the latter presumably leading to previously reported volatilome changes. Further network analyses confirmed stress-like response with activation of jasmonic acid and downregulation of gibberellic acid signalling, illuminating the possibility that the observed growth penalty was not solely a consequence of a higher metabolic burden imposed upon constitutive expression of a heterologous biosynthetic pathway, but rather the result of signalling pathways perturbation. Our work presents an example of comprehensive transcriptomic analyses of disadvantageous stress signalling in N. benthamiana biofactory that could be applied to other bioproduction systems.